Characterization of hyperpolarization-activated cyclic nucleotide-gated channels in oligodendrocytes - Lyman, Kyle A.; Han, Ye; Robinson, Andrew P.; Weinberg, Samuel E.; Fisher, Daniel W.; Heuermann, Robert J.; Lyman, Reagan E.; Kim, Dong Kyu; Ludwig, Andreas; Chandel, Navdeep S.; Does, Mark D.; Miller, Stephen D.; et al. (Frontiers in Cellular Neuroscience, 2024)
Mature oligodendrocytes (OLG) are the myelin-forming cells of the central nervous system.Recent work has shown a dynamic role for these cells in the plasticity of neural circuits, leading to a renewed interest in voltage-sensitive currents in OLG. Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels and their respective current (Ih) were recently identified in mature OLG and shown to play a role in regulating myelin length. Here we provide a biochemical and electrophysiological characterization of HCN channels in cells of the oligodendrocyte lineage. We observed that mice with a nonsense mutation in the Hcn2 gene (Hcn2 ap/ap ) have less white matter than their wild type counterparts with fewer OLG and fewer oligodendrocyte progenitor cells (OPCs). Hcn2 ap/ap mice have severe motor impairments, although these deficits were not observed in mice with HCN2 conditionally eliminated only in oligodendrocytes (Cnp cre/+ ; Hcn2 F/F ). However, Cnp cre/+ ; Hcn2 F/F mice develop motor impairments more rapidly in response to experimental autoimmune encephalomyelitis (EAE). We conclude that HCN2 channels in OLG may play a role in regulating metabolism.